A Comparative Study of Total Tannin Contents and Antimicrobial Activities in Methanol Extracts of Rhizophoraceae Species - Indriaty, Indriaty; Ginting, Binawati; Hasballah, Kartini; Djufri, Djufri (Heca Sentra Analitika, 2023)
Rhizophoraceae is a large true mangrove family that produces mangrove tannins. Tannins have the potential to be used as antimutagenic, anticancer, antimicrobial, and antioxidant agents in the pharmaceutical and medical fields. The aim of the research was to determine the total tannin content, antimicrobial activity, and the correlation between the two in methanol extracts of four plant parts (roots, bark, leaves, and fruit/hypocotyl) from five Rhizophoraceae species, namely Bruguiera cylindrica, Bruguiera gymnorrhiza, Ceriops decandra, Rhizophora apiculata, and Rhizophora mucronata originating from the Langsa mangrove forest, Aceh, Indonesia. Folin Ciocalteu colorimetric method and tannic acid as a standard were used for the total tannin content (TTC) test. The disc diffusion method was used to conduct antimicrobial tests against Escherichia coli, Staphylococcus aureus, and Candida albicans bacteria at a 50% extract concentration. TTC content in Rhizophoraceae ranged from 8.17 ± 1.36 mg TAE/g to 813.35 ± 18.72 mg TAE/g (p < 0.05). The highest levels were found in C. decandra roots (813.35 ±18.72 mg TAE/g), C. decandra bark (704.36 ± 12.11 mg TAE/g), and R. apiculata bark (651.23 ± 2.36 mg TAE/g). The extract has moderate to strong antibacterial activity against gram-positive bacteria S. aureus, with an inhibition zone range of 6.64 ± 0.80 mm -15.02 ± 0.32 mm. The highest antibacterial activity was observed in the inhibition zones for S. aureus bacteria, with C. decandra fruit extract (15.02 ± 0.32 mm), R. apiculata bark (14.78 ± 0.90 mm), and C. decandra leaves (14.44 ± 1.18 mm) exhibiting the highest levels. TTC and antibacterial activity of S. aureus in Rhizophoraceae extracts showed a moderate correlation (Pearson correlation coefficient r = 0.566, p < 0.05). According to the results, it was concluded that Rhizophoraceae has the potential to produce optimal tannins that can be used as antibacterial agents against S. aureus.